Empathising and Defining the Strategy Development Process Adoption of Industrial 4.0 in SMEs - Kurniawanti Kurniawanti; Subagyo Subagyo; Muhammad Kusumawan Herliansyah; Andi Sudiarso (School of Industrial and System Engineering, Telkom University, 2023)
The advent of Industry 4.0 has become an integral part of the manufacturing industry, playing a crucial role in boosting competitiveness and enhancing productivity within companies. Small and Medium Enterprises (SMEs), which contribute significantly to the national economy, must inevitably embrace the adoption of Industry 4.0 technology. However, the implementation of this technology at the SME faces numerous obstacles. To address these challenges and facilitate the transformation to Industry 4.0 in SMEs, this research aims to construct a comprehensive adoption strategy. Currently in its preliminary stage, the strategy development process primarily involves identifying stakeholders, their needs, and the goals they aim to achieve. Design thinking, specifically the empathize and define phase, is employed as the methodological approach. The information utilized in this study originates from systematic literature reviews conducted using PRISMA. The analysis of the gathered data has identified several stakeholders, including government entities, IT experts, management personnel, and employees. However, for the purpose of creating user personas, the focus is narrowed down to management and employees. User personas are instrumental in understanding the goals and potential obstacles faced by these individuals. The culmination of this stage is the formulation of a problem statement, which will be further refined in subsequent phases of the design thinking process.